Modeling and Calculating of Residual Stress and Strain of Butt Welded Joint - Nguyen, Tien Duong (JST: Engineering And Technology For Sustainable Development, 2021)
The non-uniform thermal expansion and contraction resulting from welding processes causes residual stresses and strains. Experimental studies to measure welding residual stresses and strains of structure are costly and sometimes they are not possible. Previously, analytical methods with idealized models were developed to determine the welding residual stresses and strain. Recently, numerical methods are constructed to analyze the stresses and the strains in welded structures. This paper presents the calculation results of residual stress and welding strain in butt welded joint of S355J2G3 carbon steel of 5 mm thickness made by MAG welding process with single pass. The calculation is performed by two methods: the imaginary force method [1] and the finite element method. In the finite element method, the SYSWELD software [2] is used to simulate and to determine residual stresses and strain of this welded joint. The results of finite element method are compared with those of imaginary force method to show the retionality and the advantages of finite element method. The study results have shown that in this welded joint, only the longitudinal and transverse stress components are important and the other stress components are negligible.